Implementasi Metode Everyone is a Teacher Here untuk Meningkatkan Keaktifan dan Hasil Belajar Sosiologi Kompetensi Ketimpangan Sosial - Sutrisna Sutrisna (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2022)
Social inequality is a sociological material that requires a deep understanding quality. Students must understand the concept and its application in people's lives. For that we need a learning method that is more active for students. This study seeks to provide information about the activity and learning outcomes of Sociology. This research will determine the effectiveness of the Everyone is a Teacher Here method, activeness and student learning outcomes. This research is a classroom action research which consists of two cycles. Each cycle includes four stages starting from planning, implementation, observation, and reflection. Based on the results of the study, it was found that (1) the implementation of the Everyone is a Teacher Here method went well, (2) there was an increase in student activity in positive activities, 37.37% experienced an increase in positive activities to 83.84%. (3) this method is able to increase the learning outcomes of Sociology on social inequality competence by 33.33%, from 57.57% to 90.91%, with an average value of 67.88 to 77.12 or an increase of 9.24%. Thus, through the application of the method Everyone is a Teacher Here has succeeded in increasing the activeness and learning outcomes of Sociology on social inequality competence.